2017
DOI: 10.1177/1088767917726807
|View full text |Cite
|
Sign up to set email alerts
|

Barriocide: Investigating the Temporal and Spatial Influence of Neighborhood Structural Characteristics on Gang and Non-Gang Homicides in East Los Angeles

Abstract: This study explored how changes in neighborhood structural characteristics predicted variation in gang versus non-gang homicides in a policing division of the Los Angeles Police Department (LAPD). Longitudinal negative binomial models were examined to test the relationship between-neighborhood structural covariates with gang and non-gang homicides over a 35-year period. This study highlights the potential to estimate temporal effects not captured by cross-sectional analyses alone. The results underscore a uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 68 publications
3
55
0
Order By: Relevance
“…C. M. Smith’s (2014) study remains the only one to empirically assess the relationship of gentrification with gang crime despite recent efforts to better understand the temporal and spatial distribution of gang crimes (e.g., see Costanza & Helms, 2012; Tita & Greenbaum, 2009; Tita & Radil, 2011; Valasik, 2014; Valasik, Barton, Reid, & Tita, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…C. M. Smith’s (2014) study remains the only one to empirically assess the relationship of gentrification with gang crime despite recent efforts to better understand the temporal and spatial distribution of gang crimes (e.g., see Costanza & Helms, 2012; Tita & Greenbaum, 2009; Tita & Radil, 2011; Valasik, 2014; Valasik, Barton, Reid, & Tita, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Violent crime rates were significantly higher in disadvantaged neighborhoods throughout all three time periods we examine. This finding, while not new (Kubrin 2003;Pyrooz 2012;Valasik, Barton, Reid, and Tita 2017), is also important as a control to our new findings about social cohesion.…”
Section: Summary and Discussionmentioning
confidence: 66%
“…Hollenbeck has a well-documented chronic gang problem stretching back over 70 years (Gustafson 1940;Valasik 2014). The overwhelming impression is a stable representation of gangs in the area (Valasik et al 2017). As many as 40 gangs were identified in Hollenbeck as of 1951 (Ranker 1957), including different age-based sets of the same gang.…”
Section: Gang Size and Violence In Hollenbeckmentioning
confidence: 99%
“…Tita et al (2004) identified 29 street gangs active in Hollenbeck in the late 1990s and early 2000s. More recent estimates identify 31 gangs (see Brantingham et al 2012;Valasik et al 2017). Thirteen of these gangs present in recent surveys are tied to the Lincoln Heights, Montecito Heights and El Sereno neighborhoods, North of the 10 Freeway.…”
Section: Gang Size and Violence In Hollenbeckmentioning
confidence: 99%
See 1 more Smart Citation